IDENTIFIKASI BUSINESS PERFORMANCE UKM DENGAN SKEMA KLASIFIKASI INTELLECTUAL CAPITAL - Arraniri, Iqbal (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2020)
When a company tries to find a business performance formula that can become a new solution in order to maintain its survival, then it depends on how its ability to manage its assets. So this study aims to examine the relationship of three main components of Intellectual Capital and Business Performance from Bontis at al: Human Capital, Structural Capital, Relational Capital. Hypothesis testing is conducted on the positive relationship between Human Capital and Business Performance, the positive relationship between Structural Capital and Business Performance, the positive relationship between Relational Capital and Business Performance, and the positive relationship between Intellectual Capital (IC) and Business Performance. Data collection techniques using a questionnaire developed from IC sub-factors based on the Intellectal Capital Classification Scheme from Moon and Kym, given directly to respondents or managers / business owners with a sample of 30 companies, then the data collected was analyzed using the IBM 20.0 SPSS program. Positive inter-variable influences have been found accompanied by rejected hopothesis.